Profitability, Leverage, dan Tax Avoidance Perusahaan Tambang di Indonesia - Rakhmawati, Ita; Restuti, Dwi Putri (IAIN Kudus, 2022)
This study investigates the effects profitability and leverage on tax avoidance. This study used a quantitative approach supported by secondary data. The population of this study comprises all mining companies listed on the Indonesian Sharia Stock Index (ISSI). The sample was 11 companies according to the specified criteria selected by the purposive sampling method. Based on a panel data regression analysis, the results of this study indicate that profitability and leverage negatively affects tax avoidance. Overall, the model supported that profitability and leverage significantly affect tax avoidance. According to the analysis, where the tendency of tax avoidance is more influenced by profitability, the implications for a government policy related to tax avoidance practices are concentrated on the profitability aspect.